2008
DOI: 10.1007/s10964-008-9362-z
|View full text |Cite
|
Sign up to set email alerts
|

African–American Parents’ Racial and Ethnic Socialization and Adolescent Academic Grades: Teasing Out the Role of Gender

Abstract: This study examined the relationship of racial and ethnic socialization and academic achievement in a sample of 218 African American adolescents (grades 9-12; 52% girls) attending a public high school in the northeastern United States. Researchers were particularly interested in whether adolescent gender moderated the relationship between racial and ethnic socialization and academic grades. Results indicated that aspects of ethnic socialization, African American cultural values and African American heritage we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…Recent studies across diverse groups of ethnic minority youth link ethnic‐racial socialization with a broad range of outcomes, including academic performance (e.g., Bennett, ; Brown, Linver, Evans, & DeGennaro, ; Smalls, ), ethnic and racial identity (e.g., Hughes, Witherspoon, Rivas‐Drake, & West‐Bey, ; Rivas‐Drake, Hughes, & Way, ; Umaña‐Taylor et al., ), and socioemotional adjustment (e.g., Constantine & Blackmon, ; Neblett et al., ; Rivas‐Drake, ). For example, cultural socialization and preparation for bias messages have been associated with academic motivation (Hughes et al., ; Neblett, Philip, Cogburn, & Sellers, ).…”
Section: Ethnic‐racial Socializationmentioning
confidence: 99%
“…Recent studies across diverse groups of ethnic minority youth link ethnic‐racial socialization with a broad range of outcomes, including academic performance (e.g., Bennett, ; Brown, Linver, Evans, & DeGennaro, ; Smalls, ), ethnic and racial identity (e.g., Hughes, Witherspoon, Rivas‐Drake, & West‐Bey, ; Rivas‐Drake, Hughes, & Way, ; Umaña‐Taylor et al., ), and socioemotional adjustment (e.g., Constantine & Blackmon, ; Neblett et al., ; Rivas‐Drake, ). For example, cultural socialization and preparation for bias messages have been associated with academic motivation (Hughes et al., ; Neblett, Philip, Cogburn, & Sellers, ).…”
Section: Ethnic‐racial Socializationmentioning
confidence: 99%
“…Research investigating gender differences in racial socialization patterns has yielded conflicting findings, with a small number of studies detecting gender differences in the content delivered and in relationships to developmental outcomes (Brown, Linver, Evans, & DeGennaro, ; Caughy, Nettles, & Lima, ; Smalls & Cooper, ; Varner & Mandara, ). In studies that have detected gender differences, research has demonstrated that, regardless of child age, African American parents deliver more messages to boys about preparation for bias and about the realities of racial barriers in society than to girls (Bowman & Howard, ; McHale et al., ; Thomas & Speight, ).…”
Section: Racial Socialization As a Process: A Relational Communicatiomentioning
confidence: 99%
“…They effectively form a means of resilience from negative environmental factors. Recent studies have found associations between ERS (particularly cultural socialisation and preparation for bias) and academic motivations/outcomes (Bennett, 2006;Brown et al 2009;Smalls, 2009) and ERS and socioemotional adjustment (Constantine and Blackman, 2002;Hughes et al, 2006;Neblett et al al., 2008;Rivas-Drake, 2011). Other studies have found cultural socialisation and egalitarian messages as predictors of positive self-concept (Bowman and Howard, 1985;Davis and Stevenson, 2006).…”
Section: Why Use Preparation For Bias?mentioning
confidence: 99%